The Role of Wisdom on Loneliness in Single Women - Lila Pratiwi; Komariah Komariah (Universitas Muhammadiyah Sidoarjo, 2019)
The present study aims to see the role of wisdom on loneliness in single women. The research was carried out through a quantitative approach with regression statistics. A total of 100 single female undergraduate students and workers aged 18-25 years participated in this study. Data was collected through a questionnaire consisting of (1) Brief Wisdom Screening Scale by Glück at al (2013), to measure wisdom, and (2) SELSA-S (Social and Emotional Loneliness Scale for Adult) developed by Ditomasso et al (2004) to measure feelings of loneliness. The reliability value for the Brief Wisdom Screening Scale (BWSS) was 0.723, while the reliability value for Social Emotional Loneliness Scale for Adult (SELSA-S) was 0.754. The result showed there was 10.7% effects of wisdom on loneliness in single women (= 0.327 with R2 = -0.107 and p <0.001). It is concluded that there is a significant role of wisdom on feelings of loneliness. The study also proposes that individuals may lower the level of loneliness by increasing their wisdom.